1996
DOI: 10.2214/ajr.166.3.8623637
|View full text |Cite
|
Sign up to set email alerts
|

Flexor tendon tears in the hand: use of MR imaging to diagnose degree of injury in a cadaver model.

Abstract: OBJECTIVE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…For this reason, we reformatted the data into the coronal plane. Reconstruction of MRI-acquired images into different planes has been widely used clinically (10)(11)(12). We found that similar tibial cartilage volumes are obtained from the original sagittal sequence and the reformatted coronal data.…”
Section: Discussionmentioning
confidence: 82%
“…For this reason, we reformatted the data into the coronal plane. Reconstruction of MRI-acquired images into different planes has been widely used clinically (10)(11)(12). We found that similar tibial cartilage volumes are obtained from the original sagittal sequence and the reformatted coronal data.…”
Section: Discussionmentioning
confidence: 82%
“…For this reason, we reformatted the data into the coronal plane. Reconstruction of MRI‐acquired images into different planes has been widely used clinically (10–12). We found that similar tibial cartilage volumes are obtained from the original sagittal sequence and the reformatted coronal data.…”
Section: Discussionmentioning
confidence: 99%
“…Although several investigators (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) have studied ultrasonography (US), computed tomography (CT), and magnetic resonance (MR) imaging in the evaluation of flexor tendon abnormalities, diagnosis of lesions of the pulley system has been made only indirectly with the detection of a gap between the flexor tendon and the bone on sagittal CT scans and MR images, a finding referred to as the bowstring sign. This sign usually reflects an extensive abnormality of the pulley system that leaves limited or partial lesions of the system virtually undetected by means of indirect methods of visualization.…”
mentioning
confidence: 99%